Effect Of Cetyl Alcohol Variation On Formulation And Stability Of Belimbing Wuluh Leaf Extract (Averrhoa Bilimbi L.) Cream - Antonius Budiawan; Febriana Alfianingrum; Bida Cincin Kirana; Erlien Dwi Cahyani (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2026)
Belimbing wuluh (Averrhoa bilimbi L.) extract has been shown to have antioxidant activity, which can help prevent skin wrinkles. This extract also has the potential to be formulated into a cream. Cetyl alcohol is a common thickener and emulsifier in a cream formulation. This study investigated the effect of cetyl alcohol concentration variation on physical properties and stability of belimbing wuluh (Averrhoa bilimbi L.) cream preparation. The extract was formulated into three creams with different cetyl alcohol concentrations: FI (3% cetyl alcohol), FII (4% cetyl alcohol), and FIII (5% cetyl alcohol). The creams were evaluated for their physical characteristics, including organoleptic properties, homogeneity, cream type, adhesion, spreadability, pH, and viscosity. Stability was tested using a Freeze and Thaw Cycling Test over six cycles. The results of the physical evaluation showed that all three formulations were good oil-in-water (O/W) creams, with the exception of FIII, which had spreadability below the standard range. The stability test revealed that FI and FII were unstable, as indicated by changes in their adhesion, spreadability, and viscosity. In contrast, FIII demonstrated good stability across all evaluations. In conclusion, the concentration of cetyl alcohol significantly impacted the physical properties and stability of the belimbing wuluh extract cream.